Investigating nurses' knowledge and attitudes about delirium in older persons: a cross-sectional study - Papaioannou, Maria; Papastavrou, Evridiki; Kouta, Christiana; Tsangari, Haritini; Merkouris, Anastasios (My University, 2023)
Delirium is the most common emergency for older hospitalized patients that demands urgent treatment, otherwise it can lead to more severe health conditions. Nurses play a crucial part in diagnosing delirium and their competencies facilitate the appropriate treatment and management of the condition.
Keywords: Acute confusion; Attitudes; Delirium; Knowledge; Nurse